2019
DOI: 10.1038/s41598-019-50575-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the microsomal proteome of tomato fruit during ripening

Abstract: the variations in the membrane proteome of tomato fruit pericarp during ripening have been investigated by mass spectrometry-based label-free proteomics. Mature green (MG30) and red ripe (R45) stages were chosen because they are pivotal in the ripening process: MG30 corresponds to the end of cellular expansion, when fruit growth has stopped and fruit starts ripening, whereas R45 corresponds to the mature fruit. Protein patterns were markedly different: among the 1315 proteins identified with at least two uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 140 publications
(128 reference statements)
1
11
0
Order By: Relevance
“…Isoenzymes of S-adenosylmethionine-synthetase (spots 12 and 14) catalyse the biosynthesis of ethylene precursors, but this enzyme is also involved in the phenylpropanoid pathways related to components in the cell wall. Literature data report that more abundant isoenzymes of S-adenosylmethionine-synthetase were found in the MG30 stage, which is consistent with the dramatically increased ethylene production which occurs in the breaker stage (Pontiggia et al 2019). The down-regulation of these isoenzymes in our study could imply the delay of the beginning of the ripening process in the flacca mutant, but also had a negative effect on the synthesis of lignin and other secondary metabolites in the flacca fruits.…”
Section: Proteomic Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…Isoenzymes of S-adenosylmethionine-synthetase (spots 12 and 14) catalyse the biosynthesis of ethylene precursors, but this enzyme is also involved in the phenylpropanoid pathways related to components in the cell wall. Literature data report that more abundant isoenzymes of S-adenosylmethionine-synthetase were found in the MG30 stage, which is consistent with the dramatically increased ethylene production which occurs in the breaker stage (Pontiggia et al 2019). The down-regulation of these isoenzymes in our study could imply the delay of the beginning of the ripening process in the flacca mutant, but also had a negative effect on the synthesis of lignin and other secondary metabolites in the flacca fruits.…”
Section: Proteomic Analysissupporting
confidence: 88%
“…Proteomic profiling of the microsomal fraction of the tomato fruit in the mature green stage (MG30) corresponding to the end of cell expansion and the start of ripening showed an increased abundance of proteins involved in glycolysis and carbohydrate metabolism, amino acid biosynthesis and the catabolic process, the synthesis of precursor metabolites and energy, as well as proteins involved in cell wall synthesis and remodeling (Pontiggia et al 2019). Among the proteins involved in glycolysis several enzymes showed much higher abundance including enolase.…”
Section: Proteomic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The different groups showed distinct expression patterns, for example, almost all genes in group A upregulated in the roots and the expression level of group C and E genes changed notably in parallel with fruit development, suggesting these two groups may be crucial for fruit development. Indeed, lipid composition is an important feature for fruit in the development stage [50,51], with lipophilic compounds in tomato fruits participating mainly in signaling, membrane structure, and development [52,53]. The diverse expression levels of SlTGL family genes in different organs or fruits at different stages, which was also confirmed by the in-house qRT-PCR analysis (Figure 7), indicates that these genes may have specific functions in the various developmental stages of tomato organs.…”
Section: Discussionmentioning
confidence: 69%
“…From this fingerprinting of tomato fruits by UHPLC-ESI-MS, we found that GUS gene expression in rootstock had a limited effect on the production of proteins in tomato fruits. Recently, there were reports on proteomic analysis using Solanaceae plants for the study of the change of membrane proteins during ripening 83) . Our analysis using UHPLC-ESI-MS revealed that the contents of crude protein extracts were not different between the ST and SN fruits.…”
Section: Proteome Analysis In Tomato Fruitsmentioning
confidence: 99%